2021
DOI: 10.1088/1755-1315/663/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Feed production on low-lying peat and developed soils of the North-East of the European part of Russia

Abstract: The results of long-term research on the use of drained lowland peat and developed soils in feed production in the North-East of the European part of Russia are presented. The main agroecological technologies for the production of high-quality feed in soil-protective crop rotations, long-term pastures on drained low-lying peat soils and methods for using developed peatlands in intensive haymaking mode are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…On map V, an increase in the content of mobile phosphorus was found in soil layers from 0 to 80 m −1 , which can be explained in the absence of fertilizers by its biogenic accumulation, since phosphorus, as shown in the studies of T. Kulakovskaya et al, has an extremely weak migration ability, and no more than 3-5% of its total reserves is washed out [7,8,18,19]. In addition, it was shown that in shallow, weakand medium-azole peat bogs, with commercial water regime and high groundwater aquifer, they can penetrate into the subsoil and underlying layers [5,6,19], which our observations also showed.…”
Section: Layout Of Peat Charts On the Baigush Peat Deposit: Sudogodsk...mentioning
confidence: 75%
“…On map V, an increase in the content of mobile phosphorus was found in soil layers from 0 to 80 m −1 , which can be explained in the absence of fertilizers by its biogenic accumulation, since phosphorus, as shown in the studies of T. Kulakovskaya et al, has an extremely weak migration ability, and no more than 3-5% of its total reserves is washed out [7,8,18,19]. In addition, it was shown that in shallow, weakand medium-azole peat bogs, with commercial water regime and high groundwater aquifer, they can penetrate into the subsoil and underlying layers [5,6,19], which our observations also showed.…”
Section: Layout Of Peat Charts On the Baigush Peat Deposit: Sudogodsk...mentioning
confidence: 75%
“…Регулированию водного режима выработанных торфяников посвящено много работ [1][2][3][4][5][6]. Исследователи выделяют ряд особенностей этих объектов, связанных главным образом с особенностями рельефа и подстилающих пород, по причине которых управление водным режимом на них осложняется или становится не эффективным [7]. Вместе с тем, в силу гидроморфного характера таких почв, они неплохо подходят для обустройства на них систем двустороннего регулирования водного режима, посредством оборудования шлюзов на оставшейся после осушения болота гидрографической сети [3,8,9].…”
Section: Introductionunclassified